CRANIOFACIAL METASTASES OF GASTROINTESTINAL ADENOCARCINOMA: A DIAGNOSTIC CHALLENGE - Radanović, Dražen; Micić, Dušan; Drakul, Ana; Đurović, Marko; Ćurčić, Mihajlo; Rudić, Marija; Mišić Mandić, Vanja; Giljača, Sonja; Manojlović Gačić, Emilija (HEALTH CARE, 2026)
Introduction/Aims: Adenocarcinomas of gastrointestinal origin rarely metastasize to the craniofacial region. Such manifestations, especially when associated with suspected leptomeningeal involvement, are characterized by high aggressiveness and a very poor prognosis. The aim of this paper is to present a rare case of a massive craniofacial metastasis from an adenocarcinoma with an atypical presentation and a fulminant clinical course. Case Report: A retrospective analysis of the medical records of a 74-year-old female patient was performed. The patient was admitted to the Emergency Center due to a sudden disturbance in the level of consciousness. Radiology revealed a massive frontoparietal lesion with extensive destruction of craniofacial bones and invasion of the orbit, sphenoid and temporal bones, and the infratemporal fossa. No primary intraparenchymal brain lesions were observed, but radiological findings suggested leptomeningeal involvement. Metastases were also detected in the liver and vertebral bodies (Th1, L1, L3). Histopathological and immunohistochemical analysis of the craniofacial mass biopsy confirmed an adenocarcinoma with an immunophenotype indicative of gastrointestinal origin. Despite intensive multidisciplinary treatment, the clinical course was fulminant, resulting in a lethal outcome on the fourth day of hospitalization. Conclusion: Craniofacial metastases of adenocarcinoma can be the first manifestation of an occult gastrointestinal malignancy. Extensive bone destruction and suspected leptomeningeal dissemination lead to an extremely unfavorable outcome. This case highlights the importance of rapid diagnosis and a high degree of clinical suspicion in patients presenting with atypical cranial bone lesions and acute neurological deterioration.